Environmental arrangement in developing a clean, beautiful and neat village - Hatta Musthafa Adham Putra; Mafazah Noviana; Zakiah Hidayati; Eman Sukmana (Community Empowerment, 2022)
One of the RTs in Samarinda City that tries to beautify its surroundings is RT 19, Sei Keledang Village, Samarinda Seberang District. This Community Service (PkM) project takes the shape of an environmental arrangement that strives to create a clean, beautiful, and neat village by constructing physical facilities such as RT gates and signposts, as well as supplying hydroponic packages, plant pots, and garbage cans. All of the programs are well-executed and deliver the intended results. Through this Community Service, it is hoped that residents can use, maintain and care for the facilities created.